EDUKASI IPTEKS KEWIRAUSAHAAN (IbK) ERA DIGITAL - Masni, Harbeng; Rahim, Arif; Myson, Myson; Hutabarat, Zuhri; Pratiwi, Heni; Andriani, Lili; Afrila, Diliza (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
The purpose of this Community Service is an effort to create new independent entrepreneurs based on science and technology that are expected to be in accordance with their fields of knowledge in the digital era, the IbK program can be implemented in the form of entrepreneurship training. This community service method uses socialization in the form of lectures and providing materials, students. The results of this Community Service provide entrepreneurial knowledge, encourage the growth of entrepreneurial motivation, increase understanding of management (organization, production, finance, and marketing) and create business plans or business feasibility studies. The conclusion is that students know how the world works, and what their role is in society.